Analysis of the Influence of Marketing Mix (Product, Price, Promotion, and Distribution) on Consumer Satisfaction and Loyalty in Ambon City - Tahalele, Marie Chrestien; Pattipeilohy, Victor Ringhard; Alfonso, Poserattu Valence (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Business competition in the digital economy era encourages business actors to design adaptive marketing strategies through marketing mix optimization to form customer satisfaction and loyalty. In Ambon City, the characteristics of the archipelago market with a relatively high level of brand switching make the study of the influence of the marketing mix on consumer satisfaction and loyalty relevant to be examined, considering that comprehensive research in the context of Eastern Indonesia is still limited. This study aims to analyze the influence of products, prices, promotions, and distribution on consumer satisfaction, as well as the influence of consumer satisfaction on consumer loyalty in Ambon City. The study used a quantitative approach with an explanatory survey design of 30 respondents selected through purposive sampling techniques, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that only the distribution variable had a positive and significant effect on consumer satisfaction (β = 0.526; p = 0.018), while the product, price, and promotion were insignificant, with prices showing a negative direction. Consumer satisfaction was shown to have a very strong effect on consumer loyalty (β = 0.864; p = 0.000). It can be concluded that distribution efficiency is the main determinant of satisfaction in the geographical context of the archipelago, while satisfaction is the central bridge to loyalty. Business actors are advised to prioritize improving the logistics system, while further research is recommended to expand the sample and add moderation variables.